2009
DOI: 10.1017/s0022029909990343
|View full text |Cite
|
Sign up to set email alerts
|

Divergence at the casein haplotypes in dairy and meat goat breeds

Abstract: Casein genes have been proved to have an influence on milk properties, and are in addition appropriate for phylogeny studies. A large number of casein polymorphisms exist in goats, making their analysis quite complex. The four casein loci were analyzed by molecular techniques for genetic polymorphism detection in the two dairy goat breeds Bunte Deutsche Edelziege (BDE; n=96), Weisse Deutsche Edelziege (WDE; n=91), and the meat goat breed Buren (n=75). Of the 35 analyzed alleles, 18 were found in BDE, and 17 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 38 publications
(100 reference statements)
3
19
2
3
Order By: Relevance
“…Due to the great geographical distance and the reproductive isolation, an explanation is not straightforward. Our findings confirm the low haplotypic variability at the casein cluster detected by Finocchiaro et al (2008) in a different sample of GIR and NOR goats and the general assessment that goat populations show a low genetic differentiation rate (Luikart et al, 2001;Canon et al, 2006;Nicoloso et al, 2015). The severe shortage of haplotypes in the NOR breed also reflects the high geographical distance from the centre of goat domestication.…”
Section: Discussionsupporting
confidence: 88%
“…Due to the great geographical distance and the reproductive isolation, an explanation is not straightforward. Our findings confirm the low haplotypic variability at the casein cluster detected by Finocchiaro et al (2008) in a different sample of GIR and NOR goats and the general assessment that goat populations show a low genetic differentiation rate (Luikart et al, 2001;Canon et al, 2006;Nicoloso et al, 2015). The severe shortage of haplotypes in the NOR breed also reflects the high geographical distance from the centre of goat domestication.…”
Section: Discussionsupporting
confidence: 88%
“…These results are not consistent with reports in Bunte Deutsche Edelziege (0.171), Weiße Deutsche Edelziege (0.419) (Küpper et al, 2010), Girgentana dairy goats (0.008) (Mastrangelo et al, 2013), MurcianoGranadina (0.590), Malagueña (0.650), Alpinee (0.340) (Jordana et al, 1996), Hungarian milk goats (0.310) (Veress et al, 2004), Maltese (0.057) (Chessa et al, 2003), Skopelos (0.070) (Kalamaki et al, 2014), Camosciata (0.114), Orobica (0.008) (Caroli 2006), White Shorthair (0.054) and Brown Shorthair (0.085) (Sztankóová et al, 2007). Frequencies similar to those of the current study were found only in Frisa (0.200) and Verzasca (0.201) goat breeds by Caroli et al (2006).…”
Section: Resultscontrasting
confidence: 56%
“…It is known that 18 alleles of CSN1S1 gene have been identified so far, which are associated with different expression levels of αS1-CN in milk (Küpper et al, 2010). These alleles can be grouped in four classes: strong alleles (A, B1, B2, B3, B4, B', C, H, L and M) are associated with 3.5 g/L; intermediate alleles (E and I) are associated with 1.1 g/L; weak alleles (F and G) are associated with 0.45 g/L of αS1-CN content; and null alleles (01, 02 and N) are associated with the absence of αS1-CN in milk (Grosclaude et al, 1997;Ramunno et al, 2000;Ibeagha-Awemu et al, 2008;Mastrangelo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the concentration of α s1 -casein present in the milk, the variants are commonly organized into four classes: (1) "strong" variants (A, B1, B2, B3, B4, Bk, C, H, L and M) synthesized at a high level (3.5 g·L −1 per allele), (2) "intermediate" variants (E and I) synthesized at a intermediate level (1.1 g·L −1 per allele), (3) "weak" variants (F and G) synthesized at a low level (0.45 g·L −1 per allele) and (4) "null" variants (01, 02 and N) not associated with protein synthesis (for review see (Küpper et al 2010;Marletta et al 2007)). …”
Section: Introductionmentioning
confidence: 99%